ИЗ ОПЫТА РАБОТЫ КОСТАНАЙСКОГО КОЛЛЕДЖА ЗЕРЕК ПО ПОДГОТОВКЕ БУДУЩИХ УЧИТЕЛЕЙ К ИССЛЕДОВАТЕЛЬСКОЙ ДЕЯТЕЛЬНОСТИ НА ОСНОВЕ ИНФОРМАЦИОННО-КОММУНИКАЦИОННЫХ ТЕХНОЛОГИЙ - Бектурганова, Р.Ч.; Кетебаева, К.К. (My University, 2019)
Аннотация В статье актуализируется проблема подготовки будущих учителей к исследовательской деятельности на основе электронной исследовательской системы. ЭИС состоит из следующих модулей: гипертекст, продуктивный и репродуктивный уровни заданий, тесты. Abstract The article actualizes the problem of preparing future teachers for research activities based on the electronic research system. ERS consists of the following modules: hypertext, productive and reproductive levels of tasks, tests.
Fostering patriotism through research approach in training of history
From the experience of Kostanay «Сollege Zerek» in preparing future teachers for research activities based on information and communication technologies
Keywords: учитель исследователь; исследовательская работа; электронная исследовательская система; гипертекст; продуктивный и репродуктивный уровни заданий; teacher researcher; research work; electronic research system; hypertext; productive and reproductive levels of tasks